Determination of Malathion Using Corona Discharge – Ion Mobility Spectrometry with Solid-Phase Microextraction. (13th April 2018) - Mu, Ren; He, Xiuli; Gao, Xiaoguang; Jia, Jian; Li, Jianping
ABSTRACT: A corona discharge (CD) ion mobility spectrometer combined with solid-phase microextraction was constructed. The detection limit and stability of the system for malathion detection were improved using a novel sample introduction port through which the sample desorption was performed in high-temperature drift tube and the sample was introduced directly to the ionization area. The working parameters of the distance between CD needle tip and carrier gas outlet, the drift tube and carrier gas temperature, the carrier gas flow, and the voltage on CD needle were selected. When the extraction time for standard malathion was set to 5 min, the detection limit was 0.96 µg L −1 based on thrice the baseline noise, the linear range was 50–500 µg L −1, the correlation coefficient was approximately 0.9941, and the relative standard deviation was below 10%. Malathion-spiked lake water samples were analyzed using the developed system and the recovery was 92–102%. This method is suitable for the rapid detection of organophosphorus pesticide residues.